PROTEIN MARKERS OF HYPOXIA AND ANGIOGENESIS IN TEAR FLUID OF PATIENTS WITH TRAUMATIC CORNEAL INJURY - I. V. Gavrylyak; V. L. Bilous; V. V. Korsa; N. K. Greben (Biotechnologia Acta, 2022)
The aim of our study was to evaluate tear levels of some protein endpoints that can reflect intensities of hypoxia, angiogenesis and tissue remodeling in wounded cornea.